The Effect of Consumer Education on Purchasing Decisions for Halal Lipstick: The Role of Price and Quality - Maulana, Lucky Hikmat; Damayanti, Vina; Maulana, Hendri; Thalib, Hasan Haikal; Suwondo, Nanang (Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2025)
The cosmetic industry is experiencing rapid growth, as evidenced by the dominance of the Indonesian cosmetic industry in the domestic market, along with the increasing interest in the use of cosmetics that encourages manufacturers to compete in creating products that suit consumer desires. This phenomenon is reflected in the various cosmetic products available both domestically and internationally. This study aims to determine purchasing decisions influenced by the price and quality variables of halal-labeled lipstick products. The design of this study is descriptive and verification, with 92 consumers as analysis units. The data collection procedure uses literature and field studies through interviews and distributing questionnaires that have been tested for validity and reliability. The data analysis method uses multiple linear regression analysis, correlation coefficient analysis, determination coefficient analysis, and simultaneous and partial significance tests. The study's results indicate that simultaneously the price and quality variables of lipstick have a significant and positive effect on purchasing decisions. The price variable has a significant and positive effect on purchasing decisions, but the quality variable partially has no significant effect on purchasing decisions. It is recommended that manufacturers consider adjusting prices to better suit consumer preferences, and maintain their quality durability, thus further strengthening their uniqueness for use in all activities.